DESAIN DIDAKTIS PEMBELAJARAN BILANGAN CACAH KELAS II SDN 11 RAMBANG - Pebrianti Putri, Alsin; Fahriza Fuadiah, Nyiayu; Dedy, Adrianus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematics learning on whole numbers in elementary schools still faces various learning obstacles that hinder students from understanding basic number concepts. These obstacles include difficulties in continuing number sequences, writing numerals, writing number names, comparing numbers, and ordering numbers. This study aimed to identify students' learning obstacles and develop a didactical design to reduce those obstacles in learning whole numbers. The research employed the Didactical Design Research (DDR) method, consisting of prospective analysis, metapedadidactic analysis, and retrospective analysis. The participants were second-grade students of SDN 11 Rambang. Data were collected through observation, interviews, diagnostic tests, prerequisite tests, implementation of the didactical design, final tests, and documentation. The data were analyzed qualitatively through data reduction, data display, and conclusion drawing. The findings revealed five learning obstacles experienced by the students in learning whole numbers. Based on these findings, a Hypothetical Learning Trajectory (HLT) was developed as the foundation for designing a didactical learning sequence implemented in three learning meetings using number and word cards. The implementation of the didactical design reduced students' learning obstacles and improved their understanding of whole number concepts. Therefore, the developed didactical design can serve as an alternative mathematics learning design to overcome students' learning obstacles on whole numbers.